Nutrient Intake, Nutrient Digestibility, Growth Performance, and Blood Parameters of Kacang Goats with GDF9 Genotype - Kustantinah -; Arif Irawan; Tety Hartatik; Sigit Bintara; Andriyani Astuti (Veterinary Integrative Sciences)
This study aims to determine the different growth differentiation factor 9 (GDF9) genotypes in Kacang goats and their influence on the animals’ nutrient intake, digestibility, digestible nutrients, performance, and blood chemical composition. Twenty-five Kacang goats underwent PCR-RFLP using the MspI enzyme to determine their genotype. Genotyping results showed that 16 Kacang goats had the AA genotype, whereas 9 had the AC genotype. Following a completely randomized design in a 2 × 2 factorial pattern, the goats were divided into two diet groups (consisting of both genotypes): Diet 1 consisted of Elephant grass (Pennisetum purpureum) supplemented ad libitum and 400 g of concentrate, and Diet 2 was a total mixed ration. No significant interaction effect (P > 0.05) between diet and genotype on nutrient intake, digestible nutrients dry matter (DM), organic matter (OM), crude protein (CP), nitrogen free extract (NFE), neutral detergent fiber (NDF), and nitrogen of neutral detergent fiber (N-NDF), and nutrient digestibility (DM, OM, NFE, NDF, and N-NDF). However, a significant interaction effect between diet and genotype (P < 0.05) was observed for CP digestibility and blood urea nitrogen (BUN) levels. Diet 1 reduced OM consumption by 15.16%, NFE by 26.87%, and digestible NFE nutrients by 31.29% compared with Diet 2. The average daily gain and relative daily gain (%) were lower in Diet 1 compared to Diet 2. The goats with the AC genotype exhibited higher CP digestibility and had the lowest BUN levels compared with those with the AA genotype. This study concluded that providing high-quality feed to goats results in their good performance, and Kacang goats with the AC genotype demonstrates more optimal CP digestibility and performance compared with those with the AA genotype.